The Role of Visum et Repertum (VeR) and VeR Psychiatricum (Legal Study of FD Murder Cases in Jakarta, 2023) - Rospita Adelina Siregar; Dyandra Eunike Nauli Sinaga (Sekolah Tinggi Hukum Bandung, 2023)
This research aims to analyze the role of law in handling the FD death case in Jakarta and its impact on the criminal justice system. The method used is normative juridical research with a statute approach and case approach. The results showed that during the examination of the suspect, an inconsistent change in attitude led to the decision to refer to the Police Hospital. The Psychiatric VeR stated that the suspect had a mental disorder of schizophrenia depression, thus following the provisions of Article 184 of the Criminal Procedure Code. According to Article 44 paragraph (1) of the Criminal Code, the suspect's actions cannot be accounted for due to mental disability, so he cannot be convicted. This finding underlines the important role of law and psychiatry in determining the criminal responsibility of a person with mental illness, contributing to the reform of a fairer and more humane justice system.